2016
DOI: 10.1080/07448481.2016.1269111
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel analysis exploring the links between stress, depression, and sleep problems among two-year college students

Abstract: Objective This study explored the association of stress and depression with a multidimensional sleep problems construct in a sample of 2-year college students. Participants The sample consisted of 440 students enrolled in 2-year study from Fall 2011 to Fall 2013. Methods Participants in an obesity prevention study completed surveys assessing sleep, stress, and depression at baseline, 4, 12, and 24 months. Multilevel models predicting sleep problems were conducted to distinguish episodic from chronic report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 52 publications
5
56
3
3
Order By: Relevance
“…In studies of undergraduate students, those who reported poorer sleep quality or reduced sleep quantity also endorsed elevated rates of depression and/or anxiety [10,13], and those who met criteria for insomnia reported increased rates of stress, fatigue, mental health, hypnotic and stimulant use, and decreased quality of life [12]. A recent longitudinal study found that chronic stress, as well as symptoms of depression, were predictive of sleep onset insomnia and hypersomnia among second-year college students [14], another longitudinal study of college students found that stress and sleep problems were bidirectional [15], and multiple studies have demonstrated that mood disorder diagnoses are often preceded by and predicted by poor sleep [16,17]. The association between stress, disrupted sleep and mental health deserves further research attention in college populations.…”
Section: The Role Of Sleep In Maintaining Mental Healthmentioning
confidence: 99%
“…In studies of undergraduate students, those who reported poorer sleep quality or reduced sleep quantity also endorsed elevated rates of depression and/or anxiety [10,13], and those who met criteria for insomnia reported increased rates of stress, fatigue, mental health, hypnotic and stimulant use, and decreased quality of life [12]. A recent longitudinal study found that chronic stress, as well as symptoms of depression, were predictive of sleep onset insomnia and hypersomnia among second-year college students [14], another longitudinal study of college students found that stress and sleep problems were bidirectional [15], and multiple studies have demonstrated that mood disorder diagnoses are often preceded by and predicted by poor sleep [16,17]. The association between stress, disrupted sleep and mental health deserves further research attention in college populations.…”
Section: The Role Of Sleep In Maintaining Mental Healthmentioning
confidence: 99%
“…The rst and therefore strongest predictor selected into the submodel was sleep quality -how refreshed a participant felt after waking up, on their average day. Sleep quality has been consistently shown to be one of the strongest predictors of well-being, especially in young adults, with poor sleep quality being strongly linked to poor mental health outcomes including symptoms of depression (Pilcher et al, 1997;Ridner et al, 2016;Wallace et al, 2017;Wilson et al, 2014). Further, it is important to note that while sleep quality is often shown to be an important predictor of well-being, sleep quantity is not (Pilcher et al, 1997;Wallace et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep quality has been consistently shown to be one of the strongest predictors of well-being, especially in young adults, with poor sleep quality being strongly linked to poor mental health outcomes including symptoms of depression (Pilcher et al, 1997;Ridner et al, 2016;Wallace et al, 2017;Wilson et al, 2014). Further, it is important to note that while sleep quality is often shown to be an important predictor of well-being, sleep quantity is not (Pilcher et al, 1997;Wallace et al, 2017). Likewise, in our study, while sleep quality was entered into the submodels early along the feature selection trajectory, re ecting its predictive strength, sleep quantity was only entered long after any improvement in predictive accuracy was shown.…”
Section: Discussionmentioning
confidence: 99%
“…The present study had two main limitations. First, depressive symptoms are influenced by a range of different factors, such as sleep quality (Chiu et al, 2005) and life stress (Wallace, Boynton, & Lytle, 2017). These factors were not addressed in the present analyses.…”
Section: Discussionmentioning
confidence: 99%